(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the importance of the art of music in the formation of the human personality and its educational role. Music is considered as a type of art that expresses and unites the emotional states and experiences of people. As an important part of aesthetic education, music helps to develop the creative abilities of students, as well as to form their spiritual qualities. The philosophical content of music, its impact on the human psyche, its possibilities for expressing mood, its form and content are analyzed in detail. The author emphasizes the social, cultural and educational significance of the art of music and studies its impact on the human psyche.